Metabolic Syndrome (MetS), Systemic Inflammatory Response Syndrome (SIRS), and Frailty: Is There any Room for Good Outcome in the Elderly Undergoing Emergency Surgery? - Fransvea, Pietro; Costa, Gianluca; Lepre, Luca; Capolupo, Gabriella Teresa; Carannante, Filippo; Puccioni, Caterina; Costa, Alessandro; La Greca, Antonio; Giovinazzo, Francesco; Sganga, Gabriele; , on behalf of the IGo-GIPS study group (Frontiers in Surgery, 2022)
Background: patients with MetS or SIRS experience higher rates of mortality and morbidity, across both cardiac and non-cardiac surgery. Frailty asseasment has acquired an increasing importance in recent years as it predisposes elderly patients to a worse outcome . The aim of our study was to investigate the influence of MetS, SIRS and frailty on elderly patients undergoing emergency surgical procedure. Methods: we analyzed data of all patients with not malignant disease requiring an emergency surgical procedure from January 2017 to December 2020. the occurrence of MetS was identified using modified definition criteria used by NCEP-ATP III Expert Panel: obesity, hypertension, diabetes, or if medication for high trygliceride or for low HDL cholesterol was taken. Systemic inflammatory response syndrome (SIRS) was evaluated according to the original consensus study (Sepsis-1). Frailty profile has been investigated by the 5-modified Frailty Index (5-mFI) and the Emergency Surgery Frailty Index (EmSFI). Postoperative complications have been reported and categorized according to the Clavien-Dindo (C-D) classification system. Morbidity and mortality have been mainly considered as the 30-day standard period definition. Results: of the 2318 patients included in this study, 1010 (43.6%) fulfilled the criteria for MetS (MetsG group). Both 5-Items score and EmsFI showed greater fragility in patients with MetS. All patients with MetS showed more frequently a CACI index major then 6. The occurrence of SIRS was higher in the MetSG. LOS was longer in patients with MetS (MetSG 11.4±12 days vs n-MetSG 10.5±10.2 days p=0.046). MetSG have a significant higher rate of morbidity (353 (35.%) vs 385 (29.4%), p=0.005). The mortality rate in patients with MetS (98/1010, 10%) was similar to the mortality rate in patients without it (129/1308, 10%). Considering patients with MetS that developed SIRS and those that had Frailty or both, the occurrence of these conditions was associated with a higher rate of morbidity and mortality. Discussion: impact of MetS and SIRS on elderly surgical patient outcomes has yet to be fully elucidated. The present study showed a 43.6% incidence of MetS in the elderly population. Elderly patients with MetS are more fragile. Moreover, MetS has a significant impact on outcomes.